2014
DOI: 10.1158/0008-5472.can-13-1103
|View full text |Cite
|
Sign up to set email alerts
|

MET and AXL Inhibitor NPS-1034 Exerts Efficacy against Lung Cancer Cells Resistant to EGFR Kinase Inhibitors Because of MET or AXL Activation

Abstract: In non-small cell lung cancer (NSCLC) with epidermal growth factor receptor (EGFR) mutations, acquired resistance to EGFR-tyrosine kinase inhibitors (EGFR-TKI) can occur through a generation of bypass signals such as MET or AXL activation. In this study, we investigated the antitumor activity of NPS-1034, a newly developed drug that targets both MET and AXL, in NSCLC cells with acquired resistance to gefitinib or erlotinib (HCC827/GR and HCC827/ER, respectively). Characterization of H820 cells and evaluation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 27 publications
6
110
2
Order By: Relevance
“…The growing body of evidence also indicates that overexpression and/or activation of Axl is a novel mechanism to induce the acquired resistance to various anticancer drugs including cytotoxic agents and various tyrosine kinase inhibitors, especially EGF receptor inhibitors (gefitinib or erlotinib) (43,44). Consistently, our data also showed that the viabilities of cisplatin/taxol-resistant cells (A549/CisR, H460/CisR, A549/TR and H460/TR) were decreased by curcumin treatment (Figs.…”
Section: Discussionsupporting
confidence: 85%
“…The growing body of evidence also indicates that overexpression and/or activation of Axl is a novel mechanism to induce the acquired resistance to various anticancer drugs including cytotoxic agents and various tyrosine kinase inhibitors, especially EGF receptor inhibitors (gefitinib or erlotinib) (43,44). Consistently, our data also showed that the viabilities of cisplatin/taxol-resistant cells (A549/CisR, H460/CisR, A549/TR and H460/TR) were decreased by curcumin treatment (Figs.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, receptor crosstalk of MET plays a critical role in the development of resistance to EGFR family inhibitors. Amplification of MET occurs in patients with NSCLC who develop resistance to the RTK inhibitors such as gefitinib or erlotinib (11,43,44). In NSCLC cells selected for resistance to gefitinib or erlotinib in vitro, MET is amplified and activated and stimulates MET/EGFR or HER3 phosphorylation and signaling to AKT (11,25).…”
Section: Discussionmentioning
confidence: 99%
“…However, some FDA-approved or clinical molecules, developed to inhibit other kinases, were evaluated against Axl given its interest. Some potent Axl kinase inhibitors in development are described in the literature (45,46). However, as few data are available regarding their selectivity and their application as treatment, we do not describe them here.…”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%